Huge strain and energy storage density of A-site La3+ donor doped (Bi0.5Na0.5)0.94Ba0.06TiO3 ceramics. Issue 1 (January 2017) - Li, Fangfang; Liu, Yunfei; Lyu, Yinong; Qi, Yunhui; Yu, Zhenglei; Lu, Chongguang
Abstract: Lead-free ferroelectric [(Bi0.5 Na0.5 )0.94 Ba0.06 ]1− x La x TiO3 (BNBT-100 x La, 0≤ x ≤0.05) ceramics were prepared by the solid state sintering methods and the effects of La 3+ doping on ferroelectricity and electromechanical strain were systematically investigated. The X-ray diffraction analysis revealed that the crystal structure partly transformed from rhombohedral phase to tetragonal phase with the increasing of La 3+ donor doping. The long-range FE order dominant in pure BNBT was disrupted by La 3+ doping. For BNBT-3La, the largest maximum strain Smax was 0.53% with a high normalized strain d * 33 of 707 pm/V under 75 kV/cm at room temperature. Moreover, a phase transition happened at EF =46.06 kV/cm under the cycle of 75 kV/cm. In particularly, a slim and pinched P-E loop was obtained for BNBT-5La with a large energy density of 1.66 J/cm 3 at 105 kV/cm.